Socioeconomic factors associated with cessation of injection drug use among street-involved youth - Derek C. Chang; Scott E. Hadland; Ekaterina Nosova; Evan Wood; Thomas Kerr; Kora DeBeck (BMC, 2017)
Abstract Background Although the initiation of injection drug use has been well characterized among at-risk youth, factors that support or impede cessation of injection drug use have received less attention. We sought to identify socioeconomic factors associated with cessation of injection drug use among street-involved youth. Methods From September 2005 to May 2015, data were collected from the At-Risk Youth Study (ARYS), a prospective cohort study of street-involved youth in Vancouver, Canada. Multivariate extended Cox regression was utilized to identify socioeconomic factors associated with cessation of injection drug use for six months or longer among youth who were actively injecting. Results Among 383 participants, 171 (44.6%) youth reported having ceased injection (crude incidence density 22 per 100 person-years; 95% confidence interval [CI], 19-26) at some point during study follow-up. Youth who had recently dealt drugs (adjusted hazard ration [AHR], 0.50; 95% CI, 0.29-0.87), engaged in prohibited street-based income generation (AHR, 0.41; 95% CI, 0.24-0.69), and engaged in illegal income generating activities (AHR, 0.19; 95% CI, 0.06-0.61) were significantly less likely to report cessation of injection drug use. Conclusions Our findings suggest that socioeconomic factors, in particular engagement in prohibited street-based and illegal income generating activities, may pose barriers to ceasing injection drug use among this population. Effort to improve access to stable and secure income, as well as employment opportunities may assist youth in transitioning away from injection drug use. Trial registration Our study is not a randomized controlled trial; thus the trial registration is not applicable.